Transformational leadership and turnover intentions: The mediating role of employee performance during the COVID-19 pandemic - İlhami Yücel (Administrative Sciences, 2021)
The purpose of this research paper is to explain the impact of transformational leadership on employees' turnover intentions in light of the mediating role of their individual performance. More precisely, we attempt to explain (a) how TL connects to employees' turnover intentions, (b) how TL connects to employee performance, (c) how employee performance connects to turnover intentions, and (d) how employee performance mediates the connection between intentions and TL. Four hundred and seventy-eight Turkish healthcare professionals participated in this research. The results revealed that employee performance mediates the connection between turnover intentions and TL. In other words, transformational leaders encourage employee performance, which in turn decreases their turnover intentions. This research has important implications for reducing turnover in workplaces and increasing employee performance by facilitating a setting for high performance, since employees who are supported by their leaders are generally more committed to their organizations and exhibit better performance. This research answers calls to study the mediating function of the TL procedure, since the mediation clarifies the circumstances under which TL relates to the favorable results.
Keywords: 350; employee performance; transformational leadership; turnover intention